Epinephrine, magnesium, and dental local anesthetic solutions. - Meechan, J. G. (American Dental Society of Anesthesiology, 1996)
Plasma levels of magnesium were unaffected by the inclusion of epinephrine in lidocaine dental local anesthetic solutions in patients having third molar surgery under general anesthesia.